Late onset cerebellar ataxia syndrome after non-paraneoplastic Lambert-Eaton myasthenic syndrome: a case study - David P. Randall; Matthew C. Randall (BMC Neurology)
Abstract This is an unusual case of voltage gated calcium channel (VGCC) antibodies leading to two distinct and chronologically separated neurologic syndromes without the presence of an underlying neoplasm. Lambert Eaton Myasthenic Syndrome (LEMS) presented five years prior to cerebellar ataxia. Both LEMS and cerebellar ataxia were responsive to treatment, but not the same therapy. He was diagnosed with LEMS through history, exam, electromyography/nerve conduction studies (EMG/NCS) with repetitive nerve stimulation (RNS) and antibody testing. He was treated with 3,4 diaminopyridine (3,4 DAP) with an excellent response. Five years later, he developed acute ataxia. The patient required months of intensive and continued immunomodulating therapy.